CI/CD Pipeline with Vulnerability Mitigation - M K, Nalini; B S, Mahalakshmi; Khandelwal, Nevya; Pai, Nandan; L, Sharan (2023 International Conference on Recent Advances in Science and Engineering Technology (ICRASET), 2023)
Our research focuses on enhancing the CI/CD pipeline with innovative approaches for vulnerability mitigation and effective handling of dependency-based attacks. By integrating advanced security measures throughout the development stages, we identify and address vulnerabilities early on. Through rigorous monitoring and strict control of dependencies, we ensure robust protection against potential attacks. The positive outcome of our research is a fortified CI/CD pipeline that streamlines software development, reduces security risks, and enables rapid and secure software deployments, thereby enhancing overall software reliability and trust.